Flimsy but handy: Devising an algorithm as a novel approach to the pharmacotherapy of cocaine addiction - Fischer, Sebastian Karl Maximilian; Mutschler, Jochen (Fortschritte der Neurologie · Psychiatrie, 2025)
Cocaine addiction is a devastating disorder, not only for the individual but also for society. Due to the rapid increase in cocaine consumption worldwide, cocaine and its deleterious psychiatric and physical consequences have increasingly become a major focus of addiction medicine. Unfortunately, advances in the treatment of cocaine addiction cannot keep pace with the surging demand for effective, fast-acting, readily available and affordable therapies. Psychosocial and psychotherapeutic measures are still the mainstay of therapy, but many patients do not have access to or benefit sufficiently from these treatment modalities. To date, there is no pharmacotherapy that has been approved or shown to be consistently effective for cocaine addiction. Nonetheless, a fair number of promising candidate substances can be extracted from a large pool of studies and there exists enough evidence to justify the assumption that many patients are likely to benefit from at least one of these substances. We have thoroughly analyzed the literature and contributed our own research results in order to integrate clinically relevant findings into an algorithm that enables the clinician to make the current state of knowledge usable in routine practice.
Keywords: cocaine addiction; cocaine use disorder; pharmacotherapy; algorithm; ADHD